The Analysis of Code-Mixing in Comments on Instagram Post by Hyundai Motors Indonesia - Muhammad Akmal Lukman Hanafi; Otong Setiawan Djauharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study describes the existence of code-mixing in comments on Hyundai Motors Indonesia's Instagram posts. Code-mixing between Indonesian and English now commonly found among social media users. This study aims to analyze the form and function of code-mixing in the comments section of the All New Hyundai Palisade teaser video reels post on Hyundai Motors Indonesia's Instagram account. Data was collected from comments published from May 30 to June 1, 2025. The results of the study show that the form of code-mixing used generally involves the insertion of English words or phrases into Indonesian sentences. The use of code-mixing is influenced by various factors such as age, educational background, foreign language proficiency, and the context of the content displayed by the Hyundai Motors Indonesia account. The functions of code-mixing found in the comments include emphasizing meaning, clarifying information, expressing emotions, and creating a modern impression.